Cleidocranial Dysplasia: A Case Report - Haque, M Azizul; Ekram, ARM Saifuddin; Huda, M Durrul (TAJ: Journal of Teachers Association, 2009)
Cleidocranial dysplasia is an autosomal dominant disorder with a wide range of expression, characterized by clavicular aplasia or hypoplasia, retarded cranial ossification, supernumerary teeth, short stature and a variety of other skeletal abnormalities. We are reporting a case of Cleidocranial dysplasia with literature is review. doi: 10.3329/taj.v21i2.3799 TAJ 2008; 21(2): 166-169